Definition and History of Educational Curriculum Development in Indonesia (1947-2013) - Alkampary, Ahmad Iqbal; Muhlis, Wachida; Norazizah, Siti (Borneo Journal of Language and Education, 2024)
The development of the education curriculum in Indonesia (1947-2013) is very important because it reflects adaptation to changing times, community needs and national development demands. During this time, the education curriculum underwent a transformation that reflected the nation's social, political and economic dynamics. From a curriculum focused on nationalism to an emphasis on developing 21st century skills, each change reflects the government's efforts to improve the quality and relevance of education. This article aims to describe the history of the development of the Indonesian education curriculum from 1945 to the present. Curriculum improvements are carried out at least once every ten years. Because in the past ten years, it is very likely that there will be changes in various fields such as information communication technology and science. The research used is qualitative with the type of library research using the documentation method as used in data collection techniques in library research. The object of study in this article focuses on tracing the history of curriculum development in Indonesia from the beginning of independence to the present. The results of this study indicate that the curriculum in Indonesia has been developed thirteen times, namely in 1947, 1952, 1964, 1968, 1973, 1975, 1984, 1994, 1999, 2004, 2006 K13 and the Merdeka Campus. The expected positive contribution from this article is that the public is educated on the history of curriculum development in Indonesia and can be used as the basis for future curriculum development to create quality students who are ready to compete internationally.